Modified Zipper Method, a Promising Treatment Option in Severe Pediatric Immune-Mediated Neurologic Disorders. (May 2022) - Nikolaus, Marc; Kühne, Fabienne; Tietze, Anna; Thumfart, Julia; Kempf, Caroline; Gratopp, Alexander; Knierim, Ellen; Bittigau, Petra; Kaindl, Angela M.
Objective: To introduce and evaluate a modified version of the "zipper method"—a treatment strategy alternating intravenous immunoglobulin (IVIG) and plasma exchange (PLEX) first reported for 9 pediatric cases of Guillain-Barré syndrome in 2018—for treatment of severe immune-mediated neurologic disorders in children. Methods: The modified zipper method comprised longer intervals between PLEX-IVIG cycles (48 hours instead of 24 hours), more cycles (7-10 instead of 5), a consistent plasma volume exchange (instead of the original multistep approach), and variable infusion times for IVIGs (4-8 hours). The modified zipper method was applied as an individual treatment approach once standard therapy failed. The follow-up ranged from 6 months to 2 years. Cases were analyzed retrospectively. Disease severity was mainly quantified by the Guillain-Barré syndrome disability score. Results: Four children (9-15 years) with (1) Miller-Fisher syndrome, (2) Bickerstaff brainstem encephalitis, (3) common Guillain-Barré syndrome, and (4) severe acute disseminated encephalomyelitis were treated by the modified zipper method. Results for duration of mechanical ventilation (median of 12 days, interquartile range [IQR] 8-16), hospital stay (median of 23 days, IQR 22-24), and time to unaided walking (median of 22 days, IQR 21-37) outperformed previous studies with IVIG/PLEX alone or IVIG + PLEX combinations unlike the zipper method. Conclusion: The modified zipper method is associated with a low mortality, a short mechanical ventilation time, a short hospital stay, and an excellent outcome in children with severe Guillain-Barré syndrome or acute disseminated encephalomyelitis. Our regimen is streamlined for applicability. Results emphasize its robust effectiveness as an option for therapy escalation in severe neuroimmunologic diseases. Now, multicenter trials are needed to evaluate this novel treatment strategy.